The Laboratory Environment Affects the Volatiles of Fungus Gardens in the Colonies of Fungus-farming Ants - Diego Santana Assis; Ted Schultz; Skylar Brodowski; Gabriel Asher Newsome; Fabio Santos do Nascimento (Sociobiology)
The ability to recognize nestmates is critical to the ecological success of social insects. Fungus-farming “attine” ants (Formicidae: Myrmicinae: Attini: Attina) can recognize their nestmates and symbiotic fungi via chemoreception. Although it has been shown that mutualistic fungi release volatile compounds that elicit responses in fungus-farming ants, the compounds and the sensory mechanisms involved remain little studied. Here, we characterize compounds found in attine fungus gardens and explore the correlations between those compounds, fungal substrates, and the laboratory environment. We also characterize ant cuticular hydrocarbons from Atta cephalotes colonies of the same species maintained in the same laboratory conditions for two or more years. Using gas chromatography associated with mass spectrometry, we verified that both substrate (i.e., the food on which fungus gardens grow) and environmental origin may influence the volatiles the fungus releases. We found compounds related to the environment, including naphthalene. We show that the volatile profiles of fungal strains grown by Atta cephalotes are most similar to each other, whereas the profile of the fungus grown by ants in the genus Cyphomyrmex is more similar to that of their substrate than to the profiles of other cultivated fungi. Regarding cuticular hydrocarbons, we found that ants collected in the same location have more similar hydrocarbon profiles than ants of the same species collected in a different location, even if all the colonies had been maintained under the same conditions (temperature, substrate) for extended periods. Our results provide strong evidence that a combination of species genetics and environmental factors shape variations in the volatile chemical profiles of cultivated fungi. After long homogenization, ants still demonstrate a solid difference among the cuticular profiles.